Discovery and evaluation of non-taxonomic relations in domain ontologies. (11th August 2009) - Weichselbraun, Albert; Wohlgenannt, Gerhard; Scharl, Arno; Granitzer, Michael; Neidhart, Thomas; Juffinger, Andreas
The identification and labelling of non-hierarchical relations are among the most challenging tasks in ontology learning. This paper describes a bottom-up approach for automatically suggesting ontology link types. The presented method extracts verb-vectors from semantic relations identified in the domain corpus, aggregates them by computing centroids for known relation types, and stores the centroids in a central knowledge base. Comparing verb-vectors extracted from unknown relations with the stored centroids yields link type suggestions. Domain experts evaluate these suggestions, refining the knowledge base and constantly improving the component's accuracy. A final evaluation provides a detailed statistical analysis of the introduced approach.